Supplemented spaces of the functions on the Peano continua - Bazilevich , L. E. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
A description of the topology of the pair $(\tilde {C} (Π, I), C (Π, I))$ for the Peano continuum $Π$, where $\tilde {C} (Π, I)$ is the closure in the hyperspace ${\rm ехр} (Π × I)$ of the image of the space of continuous functions $C (Π, I)$ under the natural embedding, is obtained.